2007
DOI: 10.2337/dc06-0996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Supplementation on Glucose Metabolism and Lipids

Abstract: OBJECTIVE -A systematic review of the effect of chromium supplementation on glucose metabolism and lipid levels. RESEARCH DESIGN AND METHODS -A literature search was conducted in MED-LINE and the Commonwealth Agricultural Bureau. Eligible studies were English language randomized controlled trials of chromium supplement intake Ն3 weeks, with Ն10 participants receiving chromium. All trials with glucose metabolism outcomes and trials of individuals with diabetes or glucose intolerance for lipid outcomes were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(143 citation statements)
references
References 50 publications
(90 reference statements)
4
134
1
4
Order By: Relevance
“…68 Two authors used the Cochrane Collaboration review template, 11,14 and one meta-analysis was performed under contract with the Agency for Healthcare Quality and Research, with rigorous descriptions of each study. 10 Both the meta-analysis by Balk et al 10 and the first meta-analysis published in 2002 9 were published before the PRISMA guidelines were released.…”
Section: Evaluating the Impact Of Chromium On Glycemic Control Despimentioning
confidence: 99%
See 1 more Smart Citation
“…68 Two authors used the Cochrane Collaboration review template, 11,14 and one meta-analysis was performed under contract with the Agency for Healthcare Quality and Research, with rigorous descriptions of each study. 10 Both the meta-analysis by Balk et al 10 and the first meta-analysis published in 2002 9 were published before the PRISMA guidelines were released.…”
Section: Evaluating the Impact Of Chromium On Glycemic Control Despimentioning
confidence: 99%
“…In contrast, drug effects tend to be monovalent, monotonic, and larger in their effect sizes and have responses that vary in proportion to dose. 70 Standardized procedures have been developed to support provision of the evidence needed for credible systematic reviews involving dietary constituents, 10,71,72 but not all published systematic studies or meta-analyses use them.…”
Section: Evaluating the Impact Of Chromium On Glycemic Control Despimentioning
confidence: 99%
“…Positive outcomes from Cr supplementation included reduced blood glucose, insulin, glycated hemoglobin (which reflects diabetes control of previous weeks), cholesterol, and triglyceride levels and reduced requirements for hypoglycemic medication. Most of these studies used Cr picolinate because of its bioavailability [2,7].…”
Section: Chromiummentioning
confidence: 99%
“…Many studies have shown that chromium supplementation increases glucose metabolism in insulin resistant populations (16,38,51). However, when healthy subjects have been examined, it has been shown that chromium has no effect on glucose metabolism (14,70).…”
Section: Discussionmentioning
confidence: 99%
“…A meta analysis by Balk et al (16) showed that chromium supplementation is beneficial in populations with impaired insulin responses and glucose intolerance. The authors also determined that chromium supplementation is not beneficial in persons who have normal glucose tolerance.…”
Section: Chromium and Glucose Intolerancementioning
confidence: 99%